Enhancing the density of silicon carbide with the addition of nitrate-based additives - Dioktyanto M.; Aryanto D.; Noviyanto A.; Yuwono A.H.; Rochman N.T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Dense monolithic silicon carbide (SiC) was successfully sintered by hot pressing at 1750ºC for 1 h under an applied pressure of 20 MPa with the addition of a nitrate-based additive. With the addition of MgO-Y2O3 and Al2O3-Y2O3 in nitrate form, a relative density of more than 98% was achieved, while in the oxide form it was 85.0 and 96.0%, respectively. In fact, MgO-Y2O3 showed poor densification due to the eutectic temperature of 2110ºC, however, the addition of the nitrate form of MgO-Y2O3 greatly enhanced the densification. The sintering mechanism in the nitrate-based additive is liquid phase sintering, identified by the presence of an oxide phase, i.e., Y2O3 in the SiC with the addition of Al2O3-Y2O3 in nitrate form. Moreover, the addition of nitrate form suppressed the grain growth of SiC, which was believed to be due to the adequate rearrangement stage during sintering.